HISTORICAL-ASTRONOMIC PROVISION OF BIRTH AND DEATH PROPHET MUHAMMAD SAW - Anisah Budiwati (Al-Hilal: Journal of Islamic Astronomy, 2019)
This paper describes the historical aspects of astronomy born from the hijri calendar and its application in determining the date of birth and death of the Prophet Muhammad. This research uses the history-astronomy method, which is history used to discuss important events that were born and died the Prophet Muhammad SAW as a great Islamic figure. While considering astronomy is used to explain the calculation of the start of the hijri calendar and analyze the date of birth and death of the Prophet through the calculation of the hisab Ephemeris and clarification of three software (Accurate Time 5.3.9, Stary Night, and Stellarium). This research concludes the brith of the Holy Prophet SAW on Legi Monday, 14th Rabi'ul Awwal 53 BH (5th May 570 AD ) and the death that the Prophet Muhammad SAW occurred on Legi Monday, 14 Rabi'ul Awwal 11 H (8 June 632 AD).